The Impact of the Credit Crunch on Initial Public Offering Decision During the Covid-19 Pandemic in Indonesia - Dyahpitaloka, Elsa; Riyanti, Ririen Setiati (Universitas Bangka Belitung, 2023)
This study aims to analyze the impact of a credit crunch on a firm's likelihood of conducting an IPO during the COVID-19 pandemic. The study on credit crunch is still limited, the majority of which focuses on the financial crises of 1998 or 2008. Meanwhile, the credit crunch during the COVID-19 pandemic was triggered differently, beginning with the real sector rather than the financial crisis. On the other hand, the industry may take into account conducting an IPO as a solution to the issue of a capital shortage brought on by the crisis. Studies on the effects of the COVID-19 pandemic's financial crunch on Indonesian IPO businesses have never been done. When the COVID-19 crisis hit the Indonesian market, it appears from the number of IPO companies and the number of shares outstanding during IPOs in Indonesia that the decline was not as severe and that companies continued to undertake IPOs. While credit growth in the banking sector is more sensitive in Indonesia than in other nations, it nevertheless tends to slow down and even turn negative during the COVID-19 epidemic. By using the logistic regression test, the results show that when funding is becoming increasingly scarce (credit crunch), it would be increasing the probability of a company going for an IPO during the COVID-19 pandemic.